Long lost [compact disc, unabridged] - Coben, Harlan, 1962- (Coben, Harlan, 1962- Myron Bolitar novel., 2009)
Contacted by a woman with whom he had an affair years earlier, Myron Bolitar learns how she has been wrongfully accused of murdering her ex-husband, a situation that is further complicated by a long-hidden family secret.